AI-Based -Green Banking Technologies And Bank Stability –Moderating Role Of Climate Change (Journal of Namibian Studies : History Politics Culture, 2023)
An unstable banking system may result in poor economic outcomes. By using SEM techniques through SMART-PLS;  this study analyzes the data from  N=380 key respondents of banks who are actively involved in adopting green banking technologies adoption and implementing climate change initiatives (i.e., renewable energy ). This study found that the adoption of green banking technologies (i.e., chatbots, facial recognition, fraud detection ) has significantly and positively improved bank stability and bank responses to climate change initiatives, partially and positively mediated the relationship between AI-based green banking technologies and bank stability. This study has both practical and theoretical significance for managers and policymakers.